2013
DOI: 10.4014/jmb.1210.10033
|View full text |Cite
|
Sign up to set email alerts
|

Increased Microalgae Growth and Nutrient Removal Using Balanced N:P Ratio in Wastewater

Abstract: Microalgal cultivation using wastewater is now regarded as essential for biodiesel production, as two goals can be achieved simultaneously; that is, nutrient removal efficiency and biomass production. Therefore, this study examined the effects of carbon sources, the N:P ratio, and the hydraulic retention time (HRT) to identify the optimal conditions for nutrient removal efficiency and biomass production. The effluent from a 2nd lagoon was used to cultivate microalgae. Whereas the algal species diversity and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…This phenomena have found confirmation in the works of Lee et al [39] and Sepúlveda et al [14], who indicated that N removal was higher for P-added media than unbalanced N:P ratio media. To elucidate this aspect the phosphorous balance into the system was performed.…”
Section: Resultsmentioning
confidence: 61%
“…This phenomena have found confirmation in the works of Lee et al [39] and Sepúlveda et al [14], who indicated that N removal was higher for P-added media than unbalanced N:P ratio media. To elucidate this aspect the phosphorous balance into the system was performed.…”
Section: Resultsmentioning
confidence: 61%
“…However, the N/P ratios after digestion (Table 4) were between 10.3:1 and 15.7:1, which were within the proper range for effective nutrient removal by algae and their biomass growth as suggested by Li et al [35]. The optimal N/P ratio found for Chlorella vulgaris for nutrient removal was 8:1 and the optimal ratio for mixture of microalgae from lagoon was 14:1 [35,36]. The balanced nutrient load, as well as the nearly neutral pH can possibly render the effluents from anaerobic digestion of algae or co-digestion with WAS to become good sources for algae cultivation.…”
Section: Characteristics Of Digestion Liquor After Anaerobic Digestionmentioning
confidence: 76%
“…However, a significant inverse correlation (p < 0.01) exists between the biomass produced and total nitrogen concentration in the water. Several authors have reported the need for a balanced N:P ratio when using wastewater as the growth medium for microalgae for increased growth and nutrient removal [26,30]. In this study, the total nitrogen concentration far exceeded the total phosphorus concentration at the NWWTW with its optimal N:P of 44.2 exceeding the optimal range of 6.8 to 10 [28].…”
Section: Discussionmentioning
confidence: 64%
“…Compared to available fossil fuel, biofuels from microalgae is more water intensive [25] with an estimated 3726 kg of water, 0.33 kg of nitrogen, and 0.71 kg of phosphate required for the production of 1 kg of microalgae based biodiesel, if freshwater is used without recycling [26,27], and may be unsustainable for a water stressed country like South Africa. Thus, wastewater presents a solution to this dilemma as it contains nitrogen in the form of nitrates and nitrites, phosphates as well as trace metals necessary for algal growth.…”
Section: Discussionmentioning
confidence: 99%